RETROSPECTIVE STUDY OF CONDITIONS GROUPED BY BODY SYSTEMS IN PET RABBITS - Tokashiki, Erick Yuji [UNESP]; Rahal, Sheila Canevese [UNESP]; Melchert, Alessandra [UNESP]; Gonçalves, Raphael Augusto Baldissera [UNESP]; Rolim, Luna Scarpari [UNESP]; Teixeira, Carlos Roberto [UNESP] (Elsevier, 2019)
This study aimed to identify retrospectively the most commonly conditions grouped by body systems in pet rabbits presented to a reference center. Data regarding rabbit's signalment, admission circumstances, and case outcome were analyzed for a period of 6 years. From a total of 202 rabbits, the cases involved the followings body systems: 31.02% integumentary, 23.61% digestive, 16.20% musculoskeletal, 9.72% genitourinary, 6.02% respiratory, 3.24% nervous, and 0.93% cardiovascular. In sense organs were classified 9.26% of cases. Integumentary system cases presented a high prevalence of parasitism by mites (n = 24), wounds and lacerations (n = 16), abscesses (n = 14), pododermatitis (n = 6), cutaneous neoplasms (n = 4), and dermatitis in genital area (n = 3). In the digestive system, overgrowth of teeth (n = 24), gastrointestinal stasis (n = 15), and coccidiosis parasitism (n = 10) were observed. Most commonly seen in the musculoskeletal system were fractures (n = 16), followed by fractured or dislocated spine (n = 7) and osteomyelitis (n = 3). All cases of the genitourinary system were elective surgeries (n = 21). Corneal ulceration (n = 6), blepharitis (n = 4), dacryocystitis (n = 3), obstruction of nasolacrimal duct (n = 3), and cataract (n = 3) were among the most common in sense organs. The nervous system had a prevalence of cranioencephalic trauma (n = 5). The respiratory system showed prevalence of pulmonary disease (n = 12). The cardiovascular system category included 2 cases: septic shock and heart disease. In conclusion, from the main body systems that were affected, integumentary system showed the highest number of cases. Parasitism by mites showed the highest prevalence. Digestive system, which comprised the highest number of deaths, had the second highest number of submissions followed by the musculoskeletal.
Keywords: disease; disorder; lagomorph; pet